2008
DOI: 10.1080/01494920802072462
|View full text |Cite
|
Sign up to set email alerts
|

Increased Family Involvement in School Predicts Improved Child–Teacher Relationships and Feelings About School for Low-Income Children

Abstract: Family involvement in school, children's relationships with their teachers, and children's feelings about school were examined longitudinally from kindergarten through fifth grade for an ethnically diverse, low-income sample (N ¼ 329). Within-families analyses indicated that changes in family involvement in school were directly associated with changes in children's relationships with their teachers and indirectly associated with changes in children's feelings about school, with student-teacher relationships me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 47 publications
2
40
0
9
Order By: Relevance
“…Related to this point, future research should examine other explanatory factors such as the involvement of students' parents. Recent studies have revealed positive links between teachers' ratings of parental involvement and the quality of the teacher-child relationship (Dearing, Kreider, & Weiss, 2008;Hughes et al, 2005;Wyrick & Rudasill, 2009), and Dutch research suggests that there are important ethnic differences in the former (Denessen, Driessen, Smit, & Sleegers, 2001).…”
Section: Limitationsmentioning
confidence: 97%
“…Related to this point, future research should examine other explanatory factors such as the involvement of students' parents. Recent studies have revealed positive links between teachers' ratings of parental involvement and the quality of the teacher-child relationship (Dearing, Kreider, & Weiss, 2008;Hughes et al, 2005;Wyrick & Rudasill, 2009), and Dutch research suggests that there are important ethnic differences in the former (Denessen, Driessen, Smit, & Sleegers, 2001).…”
Section: Limitationsmentioning
confidence: 97%
“…Indeed, there is empirical evidence that increases in family school-based activities predict improvements in children’s feelings about school and, in turn, these improvements in feelings about school predict improvements in literacy performance (Dearing, Kreider, & Weiss, 2008; Dearing, McCartney, Weiss, Kreider, & Simpkins, 2004). Along similar lines, Xu and colleagues (Xu, Kushner Benson, Mudrey-Camino, & Steiner, 2010) demonstrated that children’s self-regulation of learning mediated positive associations between school-based involvement and children’s literacy achievement.…”
Section: Family Involvement In School-based Activities: Exceptional Bmentioning
confidence: 99%
“…A recent survey indicated that families welcome overtures from schools, with most parents eager to be more involved in their children's transition to kindergarten (McIntyre, Eckert, Fiese, DiGennaro, & Wildenger, 2007). Greater parental involvement in children's schooling is in turn linked to children's higher grades, better school attendance, more positive attitudes and behaviors, higher graduation rates, and greater enrollment in higher education (Dearing, Kreider, & Weiss, 2008; Henderson & Berla, 1994). Collaboration between parents and teachers is associated with improved communication and greater trust that in turn supports children's transition to school (Child Trends, 2001; Dockett & Perry, 2001; Kraft-Sayre & Pianta, 2000; Pianta, Kraft-Sayre, Rimm-Kaufman, Gercke, & Higgins, 2001).…”
Section: Enhancing the Transition To Kindergarten A Randomized Trial mentioning
confidence: 99%